PROSES PEMBERDAYAAN TENAGA KERJA DISABILITAS MELALUI PELATIHAN VOKASIONAL OLEH PT THISABLE ENTERPRISE UNTUK DISALURKAN SEBAGAI MITRA GOLIFE - Ramadhani, Suci; Fawzi, Indra Lestari (UI Scholars Hub, 2021)
Persons with disabilities are the group most vulnerable to discrimination in society. Discriminatory behavior causes persons with disabilities to lose access to their rights, especially in terms of getting a job. Many persons with disabilities are unable to find jobs due to low educational backgrounds and lack of skills. To ensure access to work, Indonesia has passed Law Number 8 of 2016 concerning Persons with Disabilities. In this regulation, there is an obligation for the government and companies to employ persons with disabilities. In fact, the job opportunities that must be provided to persons with disabilities have not been maximally realized because some companies are not ready to employ persons with disabilities because they have not met the specified qualifications yet. Seeing the development and advancement of technology nowadays, various fields of work that can be accessed by persons with disabilities have started to emerge. To help persons with disabilities compete in the job market that has entered the era of digitalization, it is necessary to prepare abilities and skills in the field of technology. A social enterprise company, namely PT Thisable Enterprise, is involved in empowering persons with disabilities by providing training and employment for persons with disabilities. Currently, PT Thisable Enterprise is working with an app-based company, Gojek, to employ persons with disabilities in the GoLife business vertical. This research is important to research considering that there are still not many companies that supply workers with disabilities and PT Thisable Enterprise is the first company to distribute workers with disabilities to various companies. With the existence of companies such as PT Thisable Enterprise, persons with disabilities will get helped to find work so that they can improve their quality of life for the better.